Ethnogenesis of Caucasian Muslim Tats, Tats-speaking Armenians (Armenian-Tats) and Mountain Jews in light of a number of features of their languages - Semyonov, Igor (ARAMAZD: Armenian Journal of Near Eastern Studies, 2025)
A number of features of the language of Caucasian Muslim Tats allowed A.L. Grjunberg to connect their ethnogenesis with the migration of the Persians to the Eastern Caucasus in the Late Sasanid period. According to the argument presented in this article, the migration of the ancestors of Tatspeaking Armenians and Mountain Jews to this region belongs to this same period, namely to 568. The language of the Mountain Jews is distinguished by the active inclusion of the Semitic phonemes ‘ain (‘; ע) and ḫet (ḫ; ח) in terms of Persian origin. It allows us to connect the ethnogenesis of this people with the Jews of Sasanian Iran (they switched to the Middle Persian language in the Late Sasanid period). Etymological analysis of the endoethnonym of Mountain Jews ǰuhúr leads to the same conclusion. Consonants of Semitic origin are also found in the language of the Tat-speaking Armenians, but in it the rules for their use in the transfer of Persian terms are very different from those adopted in the language of the Mountain Jews. This fact indicates that the ancestors of the Tat-speaking Armenians spoke the Semitic language before switching to Iranian, and it could not have been the Jewish version of Eastern Aramaic; they were carriers of the Syriac, which was one of the variants of Eastern Aramaic. The researchers note the proximity of the languages of the Tat-speaking Armenians and the Caucasian Muslim Tats. Therefore, the variant of the Middle Persian, to which the ancestors of the Tatspeaking Armenians switched, was close to the variant characteristic of the ancestors of the Caucasian Muslim Tats, or even was identical to it. Many Tat-speaking Armenians converted to the Muslim religion, and for this reason, in a number of dialects of the language of the Caucasian Muslim Tats (cf. the data of M.I. Gadžiev), the indicated features of the language of the Tat-speaking Armenians are preserved. In the Caucasus, the Tat-speaking Armenians were under the long influence of Armenian culture and, first of all, their religious tradition, as a result of which Armenian phonemes and numerous lexical borrowings from Armenian appear in their language.